On the use of static GPS measurements to record the tidal response of a small antarctic ice shelf (Hells Gate Ice Shelf - Victoria Land) - Bondesan, A.; Capra, A.; Gubellini, A.; Tison, Jean-Louis (1994)
info:eu-repo/semantics/published